Implementation of A Clean and Healthy Lifestyle to Increase Self Endurance for Children Aged 5-6 Years at PG-TK Panca Budi Medan - Desmila Fajaria; Ristra Sandra Ritonga; Asmidar Parapat (Yayasan Multidimensi Kreatif, 2025)
A clean and healthy lifestyle is very important to be taught to children from an early age. The school environment is one of the places where children meet and interact with many people. Therefore, it is necessary to pay attention to the implementation of a clean and healthy lifestyle at school, because it will have an impact on children's self-endurance or the child's immune system. This research aims to find out how the process of implementing a clean and healthy lifestyle at PG-TK Panca Budi Medan. This study uses a quantitative approach with. One group pre-test and post-test methods. The result of the average pretest score was 58 while the postest was 77.83, it can be seen that there is a significant increase in children's self-endurance. Data was obtained through periodic observations, questions and answers to children, and documentation. The criteria for the subject of this study are children aged 5-6 years or the Kindergarten B group. The results of this study are: the application of a clean and healthy lifestyle to increase self endurance in children aged 5-6 years is successful, the child's ability to implement a clean and healthy lifestyle, and the self endurance increases well.